2021
DOI: 10.1136/bmjopen-2020-047408
|View full text |Cite
|
Sign up to set email alerts
|

Optimising a couples-focused intervention to increase couples’ HIV testing and counselling using the person-based approach: a qualitative study in Kwa-Zulu Natal, South Africa

Abstract: ObjectivesThis qualitative study explored how to optimise a couples-focused intervention to promote couples HIV testing and counselling (CHTC).SettingCommunity setting in Kwa-Zulu Natal, South Africa.ParticipantsQualitative interviews were conducted with 20 couples who had participated in a couples-focused intervention and five staff members delivering the intervention. Partners were interviewed individually by researchers of the same gender.InterventionA couples-focused intervention comprised of two group ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The healthcare workers provided support in the form of counselling and information giving, however, some participants felt the counselling was not person centred and not addressing issues related to HIV serodiscordancy. Related to this, Morton et al ( 2021 ) identified key barriers to engaging with couples in HIV testing services and these included concerns about trust in the relationship, lack of open discussion during counselling sessions. The authors emphasise the need for optimising couple-focused interventions…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The healthcare workers provided support in the form of counselling and information giving, however, some participants felt the counselling was not person centred and not addressing issues related to HIV serodiscordancy. Related to this, Morton et al ( 2021 ) identified key barriers to engaging with couples in HIV testing services and these included concerns about trust in the relationship, lack of open discussion during counselling sessions. The authors emphasise the need for optimising couple-focused interventions…”
Section: Discussionmentioning
confidence: 99%
“…A study by Morton et al ( 2021 ) identified key barriers to engaging with couples in HIV testing services and these included concerns about trust in the relationship, lack of open discussion during counselling sessions. The authors emphasise the need for optimising couple-focused interventions…”
Section: Discussionmentioning
confidence: 99%
“…By strengthening communication and functioning within the relationship, both the Igugu Lethu and Uthando Lwethu studies aim to transform the motivation of individual partners from a focus on their own health to shared health as a couple [12]. The Igugu Lethu study aims to achieve a 40% higher proportion of couples testing for HIV together than the Uthando Lwethu study.…”
Section: Discussionmentioning
confidence: 99%
“…Concerned that, in a high HIV prevalence and continued HIV incidence setting [10], 58% of intervention couples did not choose to test together during the Uthando Lwethu study, we optimised the Uthando Lwethu intervention using the Person-Based Approach to intervention development and optimisation [11]. The details of the process of optimising the intervention have been published elsewhere [12]. In brief, a qualitative study was conducted with 20 purposively sampled couples who were formerly enrolled in the intervention arm of the Uthando Lwethu Study, and with 5 study staff who delivered intervention components, with the aim of exploring experiences of the intervention and barriers to testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation